Cyclosporine Therapy as a Rescue Treatment in Steroid Refractory Acute Severe Ulcerative Colitis: A Real Life Data From a Tertiary Center - Evirgen, Sami; İliaz, Raim and Akyüz, Filiz and Çavuş, Bilger and Göktürk, Suut and Örmeci, Aslı and Mutluay Soyer, Özlem and Baran, Bülent and Pınarbaşı, Binnur and Karaca, Çetin and et al. (Turkish Journal of Gastroenterology, 2022)
Background: Cyclosporine is a rescue treatment alternative to avoid colectomy in corticosteroid refractory acute severe ulcerative colitis. In this study, we aimed to evaluate the long-term efficacy and safety of cyclosporine therapy in acute severe ulcerative colitis patients. Methods: Acute severe ulcerative colitis (basal Lichtiger score > 10) patients who did not respond to 40 mg intravenous methylpredniso- lone therapy after 3-5 days were included in the study. The presence of clinical response and remission was assessed at 1st week, 1st, 6th, and 12th month according to the Lichtiger index. Results: In this study, 40 patients, whose steroid refractory acute severe ulcerative colitis and basal Lichtiger score > 10 points were enrolled. The median disease duration was 49.3 months (2-204). All patients received cyclosporine for 132 ± 78 days (7-270). Clinical response was obtained on seventh day in 82.5%. The clinical response rates of the first and sixth months were 72.5% and 62.5%, respectively. A total of 17/40 (42.5%) patients underwent colectomy within 1 year. In the patients who underwent colectomy, the basal LS (14.2 ± 1.9 vs 12.3 ± 1.7) (P = .002) was higher and the basal hemoglobin value (11.8 ± 2.3 vs 10.1 ± 1.5) (P = .037) was lower than those who did not undergo colectomy. Conclusion: Our findings suggest that cyclosporine treatment may be successfully and safely used in steroid refractory acute severe ulcerative colitis patients. Cyclosporine is a drug that has recently started to come up again with the introduction of new maintenance treatments. Especially in patients who develop a loss of response to infliximab therapy, or where infliximab therapy is contraindicated, or who have azathioprine intolerance, or are unresponsive. Cite this article as: Evirgen S, İliaz R, Akyüz F, et al. Cyclosporine therapy as a rescue treatment in steroid refractory acute severe ulcerative colitis: A real life data from a tertiary center. Turk J Gastroenterol. 2022;33(6):463-469.